Investigação e elucidação estrutural por LC-MS/MS e RMN ¹H de impurezas desconhecidas de Ramipril Pellet geradas em estudo de degradação forçada - Medinilha, Leonardo Piccoli (Universidade Federal de São Carlos, 2018)
The development of a pharmaceutical product comprises multidisciplinary steps, coming from compatibility studies between the active pharmaceutical ingredient (API) and the other raw material (excipients) to studies of forced degradation with the final product among others. Forced degradation studies comprise a range of assays aiming to expose the medicine to different stress conditions in order to guarantee both chemical stability of the API and the formation of degradation products (also known as impurities). The control of impurities’ formation, whether coming from the process or formed during the shelf life of the product are of such importance as they may compromise the health of patient and impact on treatment in progress. The previous understanding of the formulation enables the entire lifecycle of a pharmaceutical product, once the loss of productive lots or lots in commercialization can cause financial impacts to the manufacturers and risk to the patients. It has been found that under thermal and humid stress conditions, the API ramipril presented in the form of pellets (sucrose and corn starch microspheres) undergoes degradation reactions generating impurities above the specification limit predicted in legislation for unknown impurities. Since this condition can be correlated to stability conditions predicted in legislation (30°C and 75% relative humidity for 24 months), there is a risk to the product at the end of the study. Thus, the present work focused on the structural elucidation of two impurities using mass spectrometry techniques with sequential fragmentation and nuclear magnetic resonance. It was possible to identify the chemical structures of the majority impurities in a conclusive way, being verified a transesterification reaction between the primary alcohol of the sucrose’s fructose monomer (in its two anomeric forms) from the pellets and ramipril.
Investigation and structural elucidation by LC-MS/MS and NMR ¹H of Ramipril Pellet’s unknown impurities generated by forced degradation
Keywords: Ramipril; Impureza desconhecida; Estudo de degradação forçada; Ramipril; Unknown impurities; Studies of forced degradation; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA